Treatment With Probiotic Bacteria Does Not Diminish the Impact of a Cystoisospora suis Challenge in Suckling Piglets - Unterweger, Christine; Schwarz, Lukas; Viehmann, Miriam; von Altrock, Alexandra; Gerlach, Gerhard F.; Waldmann, Karl-Heinz; Joachim, Anja; Hennig-Pauka, Isabel (Frontiers in Veterinary Science, 2018)
Colonization of newborn piglets with beneficial and ubiquitous microorganisms in combination with colostral passive immunity is the prerequisite for development of immunity and gut maturation. In this study living strains of Clostridium perfringens type A (CpA) and non-pathogenic Escherichia (E.) coli strains harvested from healthy piglets were administered to piglets prior to first colostrum intake in order to prevent disease caused by pathogenic variants of the same bacterial species by competitive exclusion. In addition, it was investigated whether these potential beneficial colonizers were able to prevent harmful effects of infection with Cystoisospora (C.) suis as a primary invasive pathogen. In a first trial, half of the piglets from four litters were treated with a bacterial cocktail consisting of two E. coli and four CpA strains immediately after birth on two consecutive days, while the other half of the litters served as control group. In a second trial, piglets were treated following the protocol of the first trial, and additionally all piglets were infected 4 hours after the end of littering with approximately 1000 sporulated oocysts of a C. suis laboratory strain. General health, body weight development, fecal consistency and, in the second trial, oocyst excretion were monitored from birth until weaning. No adverse effects of the cocktail on the health status were observed. Treated piglets of the first trial showed a higher average daily weight gain until weaning. In the second trial, no significant differences were found with respect to average daily weight gain, fecal consistency, amount and duration of oocyst excretion assessed in daily samples. In treatment group 51.1% and in the control group 38.5% of the fecal samples were positive for oocysts in autofluorescence. The average duration of oocyst excretion was longer in treatment group (7.7 days) than in control group (5.6 days). Application of bacterial cocktail could not effectively minimize disease symptoms caused by C. suis. There was a trend toward an increase in severity of disease symptoms in treated pigs, suggesting that the synergism between CpA and C. suis was independent of the bacterial strains, but is exclusively dominated by the pathogenic effect of C. suis.